Flax : The Genus Linum - Muir, Alister D (CRC Press, 2003)
This volume is a comprehensive review of the genus covering all aspects of the taxonomy, chemistry, cultivation, pharmacology and commercial uses of flax, and includes chapters on the disease prevention potential of these plants.